Genetic Evaluation of Nutritional and Fodder Quality of Different Bamboo Species - Bhandari, M. S.; Kaushal, R.; Banik, R. L.; Tewari, S. K. (Indian Forester, 2015)
Bamboos are fastest growing plants extensively used for variety of purposes; among them are stock fodder, erosion control and shelter. As a fodder species, bamboos are not potentially investigated and research lacks the qualitative approach of nutritive value found in different species of bamboo. Therefore, work on fodder quality was carried out with fourteen species of bamboo and evaluated for genetic divergence, nutritional and forage quality parameters. Based on divergence analysis of pooled data, the 14 species of bamboo were grouped into four clusters. Cluster I had maximum number of species (7), Cluster III had four species whereas Cluster II and Cluster IV had maximum of (2) and (1) species respectively. Maximum intra-cluster distance was in Cluster II and maximum inter-cluster distance was between cluster II and IV. Correlation analysis revealed that leaf:stem ratio, biomass, crude protein content, dry matter digestibility had major contribution in determining the nutritive potential of green and dry forage yield. Bamboos biomass and nutrient distribution has enormous potential to become a quality fodder for livestock animals. Therefore, bamboo may be planted in a marginal land which makes the soil fertile and produced evergreen biomass round the year.